Rural youth and employment in Ethiopia - Schmidt, Emily; Woldeyes, Firew Bekele (International Food Policy Research Institute, 2019)
Chapter 5 focuses on Ethiopia’s land constraints and asks if this is driving youth off the farm and into the rural nonfarm economy.